2016
DOI: 10.1515/bjdm-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of three Lamiaceae essential oils against common oral pathogens

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…On the other hand, incidence of oral candidiasis, as one of the most common oral infections, continuously rises during the last decade; this is also confirmed by the number of case reports describing the colonization and infection of immunocompromised patients or denture wearers subjected to the long‐term administration of synthetic oral antifungal agents, from which drug less‐responsive or even resistant or cross‐resistant isolates have been recovered. In our previous study, we have reported three highly efficient Lamiaceae EOs against oral cavity clinical isolates from genus Candida , the C. albicans and the three less known but crucial non‐candida species, C. tropicalis , C. krusei and C. glabrata , which use to be more and more involved in the oral candida disease course; according to Akpan & Morgan, these four Candida species account for more than 80% of the all clinical isolates recovered from the human oral cavities. Hence, present results of the EOs of M. alternifolia , C. limon and P. nigrum EOs support application of EOs against bacterial and fungal infections.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, incidence of oral candidiasis, as one of the most common oral infections, continuously rises during the last decade; this is also confirmed by the number of case reports describing the colonization and infection of immunocompromised patients or denture wearers subjected to the long‐term administration of synthetic oral antifungal agents, from which drug less‐responsive or even resistant or cross‐resistant isolates have been recovered. In our previous study, we have reported three highly efficient Lamiaceae EOs against oral cavity clinical isolates from genus Candida , the C. albicans and the three less known but crucial non‐candida species, C. tropicalis , C. krusei and C. glabrata , which use to be more and more involved in the oral candida disease course; according to Akpan & Morgan, these four Candida species account for more than 80% of the all clinical isolates recovered from the human oral cavities. Hence, present results of the EOs of M. alternifolia , C. limon and P. nigrum EOs support application of EOs against bacterial and fungal infections.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly isolated bacteria in the root canals with symptomatic apical periodontitis were V. parvula (10), F. nucleatum (7), S. mitis/S. oralis (7), S. salivarius (6) and S. sanguinis (5), while in the canals with asymptomatic apical periodontitis it was S. mitis/ S. oralis (5).…”
Section: Clinical Findings and Bacterial Distribution Within The Infementioning
confidence: 99%
“…Microbiota within such canals was investigated in many studies and diversity in its constituents was confirmed [1][2][3][4] . In recent years, such investigations were in focus [5][6][7][8] , probably as they represent a good starting point in development of novel material or approach in infected root canal treatment [9][10][11] . Knowing microbiota constituents provides an opportunity to distinguish sensitivities among the pathogens, which is crucial for development of potent antibacterial agents, efficient towards all pathogens, and therefore capable to prevent reinfection.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers must always keep in mind the fact that the same mixture combination will not be equally efficiant in every bacterial species, and gold standard combination for S. aureus or E. coli must not nessery be efficiant towards E. faecalis [35]. Another question is, if clinical isolates and refferent strains will be equally susceptible to applied EOs or their mixtures, as it was not always the case, at least with oral flora microorganisms [27,28]; will the thymol / geraniol mixture be equally indiferent to both, the referent and the isolated strains of E. faecalis, stays unknown until results of a new study reviel it.…”
Section: Major Constituents Common In the Most Efficient Eosmentioning
confidence: 99%
“…Knowing all disadvantages that follow E. faecalis, it's easy to understand why it is important to find something that will effectively control this pathogen, the same time being harmless to human tissues. As the standard antimicrobial agents in endodontic treatment seems to lack in efficacy toward E. faecalis [15,16,17], in addition to the fact that great efficiency of EOs towards many pathogenic oral microorganisms are already well-documented [1,4,18,19,20,21,22,23,24,25,26,27,28], we assumed the EOs might be a good source to search for efficient alternatives.…”
Section: Introductionmentioning
confidence: 99%